Impact of stone density on the total laser time and other surgical outcomes in flexible ureteroscopy - Aso Omer Rashid; Sarwar Noori Mahmood; Mohammed Ismael Nader (Advanced Medical Journal)
Background and objectives: Several preoperative factors are assessed for the evaluation of operative time and fragmentation efficacy during retrograde intrarenal surgery. Due to limited energy capabilities, stone density is an important factor contributing to procedural time. This study aimed to evaluate the effect of stone density on the total laser time in lithotripsy.